The Moderating Effect of Smart Tourism Technologies: Tourist Destination Loyalty Success in Dili (Timor Leste) - Ximenes, Mateus; Mustika, Hindah; Pujiwat, Rutma; Abbas, Ansar (KINERJA, 2024)
The research focuses on testing and analyzing the influence of several components of tourist destination loyalty, namely tourist satisfaction, experience quality, and smart tourist technologies which as a moderator variable. The research uses a quantitative method to see the influence of each variable. The respondents of the research are from various backgrounds, with a total of 317 visitors (210 women) and (107 men) who have visited tourist attractions of places historical locations in Dili (Timor Leste). The processing data use SEM-PLS, and the results of processing data show that all hypotheses significantly influence (direct) and (indirect hypotheses: smart tourist satisfaction is able to be a good moderator variable between experience quality and tourist satisfaction). The theory implication as a development of behavior and smart technologies theory, as well as the practical implication of being a strategic policy maker for stakeholders. The novelty of the research is that experience quality is in the form of physical and non-physical experiences that have positive emotions that are felt and shared with everyone so that there is satisfaction for visitors and tourist attractions.